1975
DOI: 10.1007/bf01409286
|View full text |Cite
|
Sign up to set email alerts
|

Electronic stopping cross sections of elements and compounds for swift Li ions

Abstract: Abstract. We report on experimental electronic stopping cross sections of elements and compounds for Li ions. They are measured with the Inverted Doppler Shift Attenuation (IDSA) method with an accuracy of the order of 1 }o-In cases where comparable data from other authors exist, agreement within the limits of error is obtained. Systematic and pronounced deviations up to about 30% from Lindhard's theory are found. It turns out that Bragg's rule is generally not valid for stopping cross sections in the velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1975
1975
2004
2004

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In principle, it could be possible that one of the two AS belonging to a difference 6(AS) is zero or at least small but this is rather improbable as can be seen from the Cr-and Ta-borides and from the systematic general behaviour of the borides of the transition metals as will be discussed later. 4. A quantitative discussion of these data is not possible in a satisfactory manner at the moment.…”
Section: Analysis and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In principle, it could be possible that one of the two AS belonging to a difference 6(AS) is zero or at least small but this is rather improbable as can be seen from the Cr-and Ta-borides and from the systematic general behaviour of the borides of the transition metals as will be discussed later. 4. A quantitative discussion of these data is not possible in a satisfactory manner at the moment.…”
Section: Analysis and Discussionmentioning
confidence: 91%
“…More pronounced deviations from the additivity rule are to be expected at lower energies where the outer electrons predominantly contribute to the energy loss. Various investigations of Bragg's rule have been made with protons and alpha particles [4]. In most cases liquids or gases were used as targets.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of Dpir and DLSS gave excellent agreement for gaseous BF3 and elementary boron, while some disagreement was found for water. Neuwirth et al pointed out that the discrepancy occurring in the chemical Compounds should be put down to chemical bonding effects [9][10][11][12][13][14]. They have argued that Equation (14) be not strictly valid for chemical Compounds.…”
Section: Analysis Of Line Shapesmentioning
confidence: 95%
“…The correlation between Dpix and DLSS is illustrated in Fig. 3, where the degradation constants recalculated using the stopping cross sections measured for elementary boron and water by Neuwirth et al [9] are also shown. Comparison of Dpir and DLSS gave excellent agreement for gaseous BF3 and elementary boron, while some disagreement was found for water.…”
Section: Analysis Of Line Shapesmentioning
confidence: 98%
See 1 more Smart Citation